An Unconventional Human Ccr4-Caf1 Deadenylase Complex in Nuclear Cajal Bodies - Wagner, Eileen (American Society for Microbiology, 2007)
mRNA deadenylation is a key process in the regulation of translation and mRNA turnover. In Saccharomyces cerevisiae, deadenylation is primarily carried out by the Ccr4p and Caf1p/Pop2p subunits of the Ccr4-Not complex, which is conserved in eukaryotes including humans. Here we have identified an unconventional human Ccr4-Caf1 complex containing hCcr4d and hCaf1z, distant human homologs of yeast Ccr4p and Caf1p/Pop2p, respectively. The hCcr4d-hCaf1z complex differs from conventional Ccr4-Not deadenylase complexes, because (i) hCaf1z and hCcr4d concentrate in nuclear Cajal bodies and shuttle between the nucleus and cytoplasm and (ii) the hCaf1z subunit, in addition to rapid deadenylation, subjects substrate RNAs to slow exonucleolytic degradation from the 3′ end in vitro. Exogenously expressed hCaf1z shows both of those activities on reporter mRNAs in human HeLa cells and stimulates general mRNA decay when restricted to the cytoplasm by deletion of its nuclear localization signal. These observations suggest that the hCcr4d-hCaf1z complex may function either in the nucleus or in the cytoplasm after its nuclear export, to degrade polyadenylated RNAs, such as mRNAs, pre-mRNAs, or those RNAs that are polyadenylated prior to their degradation in the nucleus.